2000
DOI: 10.1002/jlb.67.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Rottlerin, a PKC isozyme-selective inhibitor, affects signaling events and cytokine production in human monocytes

Abstract: The implication of select protein kinase C (PKC) isoenzymes in cytokine production by human monocytes was investigated using an isozymeselective inhibitor of PKC, rottlerin. We found that lipopolysaccharide (LPS) triggers cytosol-to-membrane translocation of PKC␣ and ␦ isoenzymes, whereas phorbol ester (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
69
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 46 publications
11
69
0
1
Order By: Relevance
“…Rottlerin has an inhibitory effect against the PKC delta isoenzyme and can directly regulate several biological phenomena, such as cytokine production, cell adhesion/aggregation, and cell apoptosis. For example, Rottlerin strongly affects the response of human V gamma 9V delta 2 T cells to phosphate antigens (4), CD98-dependent homotypic aggregation (3), the down-regulation of apoptosis (27), TNF-α production (17), the shedding of IL-6 receptor alpha (IL-6Rα) (40), and the modulation of the apoptosis pathway (41). In addition, our studies revealed that nPKC controlled by Rottlerin directly affected the regulation of CD93 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Rottlerin has an inhibitory effect against the PKC delta isoenzyme and can directly regulate several biological phenomena, such as cytokine production, cell adhesion/aggregation, and cell apoptosis. For example, Rottlerin strongly affects the response of human V gamma 9V delta 2 T cells to phosphate antigens (4), CD98-dependent homotypic aggregation (3), the down-regulation of apoptosis (27), TNF-α production (17), the shedding of IL-6 receptor alpha (IL-6Rα) (40), and the modulation of the apoptosis pathway (41). In addition, our studies revealed that nPKC controlled by Rottlerin directly affected the regulation of CD93 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of macrophages with M. avium leads to the activation of PKC, and PKC in turn is involved in the activation of many genes, such as TNF-␣, IL-1, and IL-6 (27,28). PKC functions by regulating the activation of transcription factors such as NF-B, c-Fos, and c-Jun (29 -31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since ERK1/2 activation is required for PMA-dependent monocyte differentiation as shown by us here with MEK inhibition studies and by others (33), we conclude that PKC␦ is the critical PKC responsible for PMA-induced monocyte differentiation in U937 cells and that its autophosphorylation on serine 660 probably controls this process. Furthermore, from the 32D cell studies sited above, PKC␦ would be expected to play an important role, generally, in the phorbol ester activation pathway (43) in monocytes.…”
Section: Fig 2 Pma-dependent Activation Of Erk1/2 Is Regulated By Cmentioning
confidence: 99%